2018
DOI: 10.1101/252049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex Chromatin Interaction Analysis with Single-Molecule Precision

Abstract: We describe a microfluidics-based strategy for genome-wide analysis of multiplex chromatin interactions with single-molecule precision. In multiplex chromatin interaction analysis (multi-ChIA), individual chromatin complexes are partitioned into droplets that contain a gel bead with unique DNA barcode, in which tethered chromatin DNA fragments are barcoded and amplified for sequencing and mapping to demarcate chromatin contacts. Thus, multi -ChIA has the unprecedented ability to uncover multiplex chromatin int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Also, new methods have been developed to overcome the limitation of most proximity-ligation methods that can only detect pair-wise interactions as they rely on the physical ligation of neighbouring fragments-ends. Recent techniques, such as SPRITE (Split-Pool Recognition of Interactions by Tag Extension) and ChIA-Drop (Chromatin Interaction Analysis via Droplet-based and barcode-linked sequencing), can detect multiway interactions by performing a physical separation of interacting domains (in wells or in droplets, respectively) followed by pooled-tagging and sequencing (Quinodoz et al, 2018;Zheng et al, 2019). The identification of multi-way interactions and complex contacts will be particularly relevant to delve deeper into chromatin topology and supercoiling.…”
Section: Cutting-edge Sequencing and Imaging Approaches Provide New I...mentioning
confidence: 99%
“…Also, new methods have been developed to overcome the limitation of most proximity-ligation methods that can only detect pair-wise interactions as they rely on the physical ligation of neighbouring fragments-ends. Recent techniques, such as SPRITE (Split-Pool Recognition of Interactions by Tag Extension) and ChIA-Drop (Chromatin Interaction Analysis via Droplet-based and barcode-linked sequencing), can detect multiway interactions by performing a physical separation of interacting domains (in wells or in droplets, respectively) followed by pooled-tagging and sequencing (Quinodoz et al, 2018;Zheng et al, 2019). The identification of multi-way interactions and complex contacts will be particularly relevant to delve deeper into chromatin topology and supercoiling.…”
Section: Cutting-edge Sequencing and Imaging Approaches Provide New I...mentioning
confidence: 99%
“…These were more clearly confirmed by subsequent studies. For example, self-interacting domains were redefined by Micro-C under loop extrusion, which was defined in a future study as a transcription reeling-in model by ChIA-Drop [68]. Benefitting from Micro-C technology, scientists have discovered many new structures.…”
Section: Million Cells Per Reaction Mnasementioning
confidence: 99%
“…In the nuclei of multicellular eukaryotes, chromatin forms hierarchical three-dimensional (3D) structures on top of its linear conformation (Ouyang et al, 2020b). With the development of chromosome conformation capture (3C) methods (Louwers et al, 2009;Hakim and Misteli, 2012;Jamge et al, 2017;Hua et al, 2021), functional structures have been revealed at various genomic scales, including chromatin territories, A/B compartments, topologically associating domains (TADs), and chromatin loops (Meaburn and Misteli, 2007;Lieberman-Aiden et al, 2009;Dixon et al, 2012;Grob and Grossniklaus, 2017;Zheng et al, 2019). From territory to loop, the detection resolution required increases in order (Rodriguez-Granados et al, 2016).…”
Section: Introductionmentioning
confidence: 99%